2022
DOI: 10.22376/ijpbs/lpr.2020.10.4.p90-95
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Opuntia elatior on Alteration in Glutamic Oxaloacetic Transaminase activity induced by Gamma Radiation in Swiss Albino Mice

Abstract: When mice are exposed to gamma radiation, all the body systems are affected adversely. Liver enzymes which are responsible for removal of toxicity created by irradiation increases in the body. Several herbs are known to reduce this toxicity. Opuntia elatior (OE) ,a cactus, was tested in this study for its activity to remove toxins induced by whole body exposure to Co 60 gamma rays (6Gy).A moderate dose of OE (10 mg/kg body weight) was given orally to mice, before whole body irradiation and GOT activity was stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In this study, we investigated the radioprotective effect of AME as an agent shown to have anticarcinogenic, anticonvulsant, antiin ammatory, antioxidant, radioprotective (against Gamma-ray) and neuroprotective properties [10,22,28]. There are only a few studies on the radioprotective effect of AM in the literature [10,17,21]. However, these studies were not done with X-ray; The radioprotective effect of AME against gamma-ray damage was examined.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the radioprotective effect of AME as an agent shown to have anticarcinogenic, anticonvulsant, antiin ammatory, antioxidant, radioprotective (against Gamma-ray) and neuroprotective properties [10,22,28]. There are only a few studies on the radioprotective effect of AM in the literature [10,17,21]. However, these studies were not done with X-ray; The radioprotective effect of AME against gamma-ray damage was examined.…”
Section: Discussionmentioning
confidence: 99%